Design of Digital Mobile Application for Marine and Coastal Observation in Northern part of Sumatra - Matondang, Aprima A.; Simanjuntak, Mutiara; Simangunsong, Juanto (Politeknik Negeri Batam, 2024)
We have successfully developed a mobile program to address the challenges of marine and coastal observation serves as a solution to the communication gap between local peoples with ocean issues. In this app, we examine common of marine problems encountered by civilian and discuss the methods used to diagnose and resolve these issues. Some preventive measures can be taken are mangrove replanting programs, satellite and drone monitoring systems to monitor illegal activities at sea and campaigns to reduce the use of single-use plastics and raise awareness of the importance of marine conservation. These can be combined in a digital application connected to a smartphone. The application can answer future challenges related to observation and preventive measures for strengthening and mitigating disasters in marine and coastal ecosystems that can support maritime-based economic resilience in Indonesia. The application is MyOcean that can handle several problems related with ocean issues. The following displays the home page and registration page on the web-based boarding search application. By utilizing these applications, users can improve their understanding, management, and preservation of coastal areas. These applications are suitable for various groups, including fishermen, government, and the general public.